Tathwîri Ta'âlîmi Al-Qur'ân Al-Karîm - Zainap Hartati (Jurnal Hikmatuna, 2017)
The Duties of Quranic Education The decline in the number of Muslims and the lack of interest in religious studies were ironic for State Islamic Universities (UIN) which one of its universities bears the name Walisongo (i.e., nine medieval saints who spread Islam in Java). The Islamic propagation of Walisongo evidently aimed at Islamizing the Javanese island, producing religious scholars, and establishing an Islamic society. The religious faculties at UINs, which are the continuation of Walisongo's efforts in propagating Islamic teachings, have recently diminished. The purpose of this research was to analyze the causes of students' low interest in the religious faculties at UINs and relate them to the spirit of Walisongo's undertakings. This study was a literature review using a qualitative approach that did not involve quantitative data calculation. The study concluded that the existence of religious faculties at UINs aligns with Walisongo's goal of spreading Islam through educational institutions. The religious faculties, which can be regarded as a continuation of Walisongo's struggle in propagating Islam, consist of four faculties: Adab (Humanities), Ushuluddin (Islamic Theology), Syari'ah (Islamic Law), and Da'wah (Islamic Propagation). In a special case at UIN Jakarta, there is the Faculty of Islamic Studies in cooperation with Al-Azhar University in Cairo. The faculties of religiosity had their golden age during the IAIN period but have been declining throughout the UIN period. The decline was assessed by the indicator of the decreasing number of students, particularly compared to the number of students enrolled in secular faculties at UINs.